Epigenetic cellular memory in Pseudomonas aeruginosa generates phenotypic variation in response to host environments - Vatareck, Elisabeth; Rick, Tim; Oswaldo Gomez, Nicolas; Bandyopadhyay, Arnab; Kramer, Janina; Strunin, Dmytro; Erdmann, Jelena; Hartmann, Oliver; Alpers, Kathrin; Boedeker, Christian; Steffen, Anika; Sieben, Christian; et al. (Proceedings of the National Academy of Sciences - PNAS, 2025)
Phenotypic diversification within pathogen populations can enhance survival in stressful environments, broaden niche colonization, and expand the ecological range of infectious diseases due to emerging collective pathogenicity characteristics. We describe a gene regulatory network property in the opportunistic pathogen Pseudomonas aeruginosa that generates diversity of gene expression and pathogenicity behavior at the single-cell level and that is stabilized by epigenetic cellular memory. The resulting heterogeneity in the expression of the glpD gene—an indicator of host-derived glycerol metabolism and intra-host presence—shapes adaptive processes that are subject to natural selection. Our work on how epigenetics generates phenotypic variation in response to the environment and how these changes are inherited to the next generation provides insights into phenotypic diversity and the emergence of unique functionalities at higher levels of organization. These could be crucial for controlling infectious disease outcomes.